High-order harmonic generation driven by plasmonic fields: a new route towards the generation of UV and XUV photons?. (March 2015) - Ciappina, M F; Pérez-Hernández, J A; Roso, L; Zaïr, A; Lewenstein, M
Abstract: We present theoretical investigations of high-order harmonic generation (HHG) resulting from the interaction of noble gases with different kind of temporally and spatially synthesized laser fields. These fields, based on localized surface plasmons, are produced when, for instance, a metal nanoparticle or nanostructure, is illuminated by a few-cycle laser pulse. The enhanced field, which largely depends on the geometrical shape of the metallic nanostructure, has a strong spatial dependency in a scale comparable to the one where the electron dynamics takes place. We demonstrate that the spatial nonhomogeneous character of this laser field plays an important role in the HHG process and leads to a significant increase of the harmonic cutoff energy and modifications in the electron trajectories. The use of metal nanostructures appears to be an alternative way of generating coherent XUV light with a laser field whose characteristics can be spatially synthesized locally.